A Literature Review on Strategic Business Communication for Managerial Effectiveness in the Digital Era - Sukoco, Hendro; Krisnaresanti, Aldila; Budiman, Asep (Journal of Office Administration : Education and Practice, 2024)
In the rapidly evolving digital era, strategic business communication has become a pivotal element of effective managerial practice. The primary objective of this study is to examine the relationship between strategic communication approaches and managerial effectiveness, particularly in light of the growing influence of digital transformation and remote work environments. The study employs a structured literature review method, systematically identifying, analyzing, and synthesizing peer-reviewed journal articles from reputable databases such as Scopus, Web of Science, and ScienceDirect, published over the past decade (2013–2023). The review process follows the PRISMA protocol to ensure transparency and rigor in data collection and synthesis. This study underscores that communication in the digital era is no longer a linear process but a complex, interactive, and context-dependent managerial function. Effective communication enhances trust, coordination, adaptability, and innovation—particularly vital in remote or hybrid organizational settings. This study contributes to the understanding of communication as a core managerial competency and offers practical recommendations for navigating contemporary communication challenges.